THE ROLE OF SPOUSAL SUPPORT, PERFECTIONISM, AND MARITAL SATISFACTION IN POSTPARTUM DEPRESSION - Rina Afrina; Aisyah Safitri; Yuyu Nengsih (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Spousal social support, marital satisfaction, and perfectionism can be causes of depression in mothers. This study analyzes the relationship between spousal social support, perfectionism, and marital satisfaction with the occurrence of depression in mothers after childbirth. The cross-sectional study design used 60 postpartum mothers as samples, collected over two months (April–May) using accidental sampling techniques. Bivariate analysis was conducted using the chi-square test with SPSS Statistics V26. The results showed that 30% of the mothers were aged 20–25 years, 41.7% had a history of one childbirth, 86.7% were housewives, and mothers married for over 10 years (28.3%), and normal delivery (49.4%). The results of the bivariate analysis using the chi-square test showed that spousal social support (0.002), marital satisfaction (0.013), and perfectionism (0.000) were associated with the occurrence of depression in mothers (<0.05). It can be concluded that there is a relationship between spousal social support, perfectionism, marital satisfaction, and the occurrence of postpartum depression in mothers.